Programma: 14 januari Inés Arrubla y Grupo Flamenco; 15 januari DJ's on a mission; 16 januari Cuba cultura; 18 januari The Congos
Programma: 14 januari Inés Arrubla y Grupo Flamenco; 15 januari DJ's on a mission; 16 januari Cuba cultura; 18 januari The Congos.